Mouse model of imiquimod-induced psoriatic itch. Issue 11 (November 2016) - Sakai, Kent; Sanders, Kristen M.; Youssef, Marina R.; Yanushefski, Kevin M.; Jensen, Liselotte; Yosipovitch, Gil; Akiyama, Tasuku
Abstract : Abstract: Itch is a major indicator of psoriasis, but the underlying mechanisms behind this symptom are largely unknown. To investigate the neuronal mechanisms of psoriatic itch, we tested whether mice subjected to the imiquimod-induced psoriasis model exhibit itch-associated behaviors. Mice received daily topical applications of imiquimod to the rostral back skin for 7 days. Imiquimod-treated mice exhibited a significant increase in spontaneous scratching behavior directed to the treated area as well as touch-evoked scratching (alloknesis). To characterize this model, we measured the mRNA expression levels of pruritogens and itch-relevant receptors/channels using real-time reverse transcription PCR. The mRNA expression of MrgprA3, MrgprC11, and MrgprD decreased gradually over time in the dorsal root ganglion (DRG) cells. There was no significant change in the mRNA expression of TRPV1 or TRPA1 in DRG cells. TRPV4 mRNA expression was transiently increased in the DRG cells, whereas TRPM8 mRNA was significantly decreased. The mRNA expression levels of histidine decarboxylase and tryptophan hydroxylase 1, as well as the intensity of histamine and serotonin immunoreactivity, were transiently increased in the skin on day 2, returning to baseline by day 7. Histamine H1-receptor antagonists, chlorpheniramine and olopatadine, significantly inhibited spontaneous scratching on day 2, but not day 7. Neither chlorpheniramine nor olopatadine affected alloknesis on day 2 or day 7. These results may reflect the limited antipruritic effects of histamine H1-receptor antagonists on human psoriasis. The imiquimod-induced psoriasis model seems to be useful for the investigation of itch and its sensitization in psoriasis. Abstract : Mice treated with imiquimod-developed psoriasis-like dermatitis and behavioral signs of chronic itch that are insensitive to histamine H1-receptor antagonists.